Peut-on modéliser les activités physiques en éducation physique et sportive en termes de problématisation ? L’exemple de la course de haies - Alain Le Bas (Recherches en Éducation)
This contribution questions the results of a previous research in didactics of hurdle racing (INRP, 1995). We will proceed using the theory of problematization to test the theoretical hypotheses which constitute the five main characheristics of problematization such as they have been defined by M. Fabre.: - A multidimentional process, involving problem positioning, problem building and problem solving, - A process of searching from the unknown to the known, - A dialectic procedure funded on facts, ideas, experiences and theories, - A theoretical thinking delimited by intellectual, technical and programatical norms, - A functional modelisation allowing an approach to reality without pretending to describe and reproduce reality as a whole. We believe that the multidimentional process represents the characteristic of the activity of problematization in so far as it describes its various operations, the pre-defined norms at work appear as constraints definining the field of problematization and the other dimensions of the original proposition are the conditions of the fonctionality of the process. The adaptibility of the psychomotor behaviours expresses itself in the capacity to identify, to characterize and to solve a problem, to provide adequate stable responses, to identify a problem for which a solution has been found. We will try to see how Physical Education and more particularly hurdle racing, by taking into acccount problematization, can lead to a renewed approach of learning processes and make them operational.